The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1055/s-0036-1590925
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Chemoselective Synthesis of α-Chloro and Vinyl Sulfones by Sulfonylation of Alkenes

Abstract: Direct sulfonylation between alkenes and sulfonyl chloride was achieved at room temperature by a visible-light-induced photo­redox process. This method allows the chemoselective synthesis of α-chloro and vinyl sulfone derivatives with moderate to high yields. The selectivity of the reaction was fully controlled by the electronic properties of the alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…Also, in 2018, Kim and Han reported the same chlorosulfonylation observed by Niu and Ni for electron-rich alkenes 40 but employing internal and terminal arylacetylenes as coupling partners. 41 Notably, both aliphatic and aromatic sulfonyl chlorides yielded the desired product.…”
Section: Scheme 21 Photocatalyzed Synthesis Of -Hydroxy Sulfones From Various Sulfonyl Chlorides and Styrenesmentioning
confidence: 58%
See 1 more Smart Citation
“…Also, in 2018, Kim and Han reported the same chlorosulfonylation observed by Niu and Ni for electron-rich alkenes 40 but employing internal and terminal arylacetylenes as coupling partners. 41 Notably, both aliphatic and aromatic sulfonyl chlorides yielded the desired product.…”
Section: Scheme 21 Photocatalyzed Synthesis Of -Hydroxy Sulfones From Various Sulfonyl Chlorides and Styrenesmentioning
confidence: 58%
“…In 2018, Niu examined these two possibilities reporting a chemo-selective synthesis of αchloro sulfone 69a and vinyl sulfone derivatives 69b. 39 The author reacts arylsulfonylchlorides 57 with alkenes 68a and 68b in the presence of Ru(bpy)3Cl2•6H2O as the photocatalyst under blue light irradiation. Interestingly, they demonstrated that electrondonating substituents on the alkenes 68b direct the reactivity towards the formation of vinyl sulfones 69b whereas electronwithdrawing groups yielded β-chloro sulfones 69a (Scheme 27).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Much to our surprise, this methodology was never applied to unsaturated compounds with double or triple carbon-carbon bond as nucleophilic site and sulfonyl chloride as electrophile. Although intermolecular addition of sulfonyl chlorides to olefins under free-radical conditions (atom transfer radical addition) is well documented and widely used for the preparation of α-chloro sulfones and vinyl sulfones (see e.g., [ 25 , 26 , 27 , 28 , 29 ] and references therein), there is only one publication reporting small-scale homolytic intramolecular heterocyclization of pent-4-sulfonyl chloride proceeding at high temperature (AIBN-CuCl 2 , MeCN, 170 °C) and resulting in 3-chlorotetrahydrothiopyran 1,1-dioxide in a low yield (17%) [ 30 ]. Obviously, this heterocyclization is of low preparative value and has rather theoretical meaning.…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, Ni group found that different products were isolated from the visible light induced sulfonylation reaction of alkenes and sulfonyl chloride [90] . The selectivity of the reaction was fully controlled by the electronic properties of the alkenes.…”
Section: Sulfonylation Reaction Using Sodium Sulfinatesmentioning
confidence: 99%